Peran dukungan sosial dalam menghadapi fase quarter life crisis dewasa awal penyandang disabilitas fisik - Azwa Salsabila Anggraeni; Udi Rosida Hijrianti (Fakultas Psikologi, 2023)
Early adulthood is a time when individuals will experience complex developmental problems related to the role of adults and the underlying psychological processes. Persons with disabilities are someone who experiences physical or sensory limitations for a long time, called physical limitations if the individual loses (all or part) his body functions motorly, activities such as fine motor skills, talking, walking, hand movements and so on. At this time individuals will tend to have negative feelings such as feelings of uncertainty, anxiety, anxiety, and frustration which is usually called the quarter life crisis phase. Social support is a feeling of comfort, attention, and assistance received by individuals from other individuals. The purpose of this study was to determine the effect of social support and quarter life crisis on early adults with disabilities. This study used a descriptive quantitative technique on 102 participants. The research subjects were taken using a purposive sampling technique with the criteria for early adulthood persons with physical disabilities, male or female, aged 18-25 years. The instruments in this study consisted of the Multidimensional Scale of Perceived Social Support (MSPSS) and the Quarter Life Crisis Scale. The results showed that there was an effect of social support on quarter life crises in early adulthood with disabilities (r = .053; p = .020 <.05). Keywords: Early adulthood, quarter life crisis, physical disabilities, social support